Development of STEM-Based Science Learning Integrating Local Wisdom through Interactive Pop-Up Book in Elementary Schools - Sumadi, Conny Dian; Setyawan, Agung Setyawan (Widyagogik, 2024)
This study aims to develop STEM-based science learning devices integrated with Madurese local wisdom through interactive pop-up book media for elementary school students. The background of this study is the limited use of contextual learning resources and innovative media in elementary science instruction, which affects students’ engagement and conceptual understanding. This research employed a Research and Development (RD) method using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. The developed learning devices included teaching modules, interactive pop-up books, student worksheets, and assessment instruments. The validation results from material experts, media experts, and learning experts indicated that the learning devices were highly valid. Student responses showed a very positive perception of the learning process, and learning outcomes improved after the implementation of the developed devices. The integration of STEM principles with Madurese local wisdom—such as coastal ecosystems, salt production, and fishermen’s activities—made science learning more meaningful and contextual. Therefore, the developed STEM-based science learning devices integrated with local wisdom are feasible and effective for use in elementary school science learning.